Design of indoor positioning method jointly assisted by RIS and IMU - SUN Wei; DU Xin; SONG Qingyang; GUO Lei (Tongxin xuebao)
To address the issue of excessive pilot overheads in reconfigurable intelligent surface (RIS)-assisted positioning techniques, a joint RIS and inertial measurement unit (IMU)-assisted indoor positioning method was proposed, aiming to achieve continuous and accurate positioning for a indoor mobile user equipment (UE). Firstly, the measurement data provided by the IMU was used as a piece of priori location information to guide the fine-grained phase shift configuration of the RIS, thereby reducing the overheads required for channel parameter estimation. Then, the factor graph optimization approach was applied to integrate the IMU’s measurement data with the phase shifts of the RIS, constructing an optimization problem for position estimation. Finally, the Levenberg-Marquardt algorithm was employed to solve the optimization problem and estimate the UE’s position. After that, the IMU data was calibrated and errors were compensated, both based on the fused positioning results. Simulation results demonstrate that the proposed method offers higher positioning accuracy and requires less pilot overheads compared to existing methods.